多分量地震监测系统AETA的感应式磁传感器磁棒研制 - Yong, Shanshan; Wang, Xin'an; Pang, Ruitao; Jin, Xiuru; Zeng, Jingwu; Han, Chaoxiang; Xu, Boxing (Beijing da xue xue bao, 2018)
According to the multi-component seismic monitoring system's technology requirements, an inductive magnetic sensor is presented and the design analysis and industrial implement are discussed. According to the requirements of electromagnetic disturbance monitoring, the authors define the design parameters and propose a well-considered plan on materials choosing and architecture designing. The covered frequency range is 0.1 Hz-10 kHz, the temperature range is -40-130°C, the monitoring range of magnetic field strength is 1-1000 nT, and the sensitivity requirement is larger than 20 mV/nT@(0.1 Hz-10 kHz). The final test shows that the performance is achieved. This sensor is applied in multi-component seismic monitoring system which is being installed widely.